Pengaruh Parameter Pemotongan Pembubutan Konvensional Terhadap Kekasaran Permukaan Baja ST41 - Ahmad Rifai; Syaripuddin; Anggrainy, Rani; Agung Premono; Ferry Budhi Susetyo (Universitas Nusa Putra, 2023)
The turning process is essential in the manufacturing industry to produce a product. The quality of a product is greatly influenced by the turning process, which produces varying roughness characteristics of the product's surface. The selection of suitable cutting parameters greatly influences the surface roughness of the product from the turning process. Therefore, a study was carried out on the cutting parameter's effect on the workpiece's surface roughness. In this research, the material used was ST 41 steel with a diameter of 25.4 mm. The turning process uses a conventional lathe. Variation in this study is the cutting speed and feeding depth. The results showed that the higher the cutting speed, the smaller the surface roughness value. On the contrary, the greater the feeding depth, the greater the surface roughness value.